Lebih Cepat, Lebih Hemat, Lebih Untung: Efektivitas Teknologi Ultrasonik pada Budidaya Nila Red Bangkok di Pokdakan Rejoayu - Okimustava; Moh. Toifur; Destri Ratna Ma’Rifah; Hendro Setyono; Bambang Sudarsono; Eko Susanto (JURPIKAT, 2025)
The community service program on red Bangkok tilapia farming at Pokdakan Rejoayu aims to enhance members’ skills, production efficiency, and pest control through the application of ultrasonic technology. The main challenges faced by the partner group are limited technical knowledge, high feed costs, and frequent attacks from otters and herons. The program activities included socialization, training, application of ultrasonic devices, and continuous assistance. Preliminary results show an increase in members’ skills from 25% to 80%, representing a 55% improvement. The use of ultrasonic devices reduced pest attacks by 50–60% and increased the survival rate of fish from 60–65% to 75–80%. Growth performance also improved, with the harvest period shortened by approximately one month. In addition, the use of locally based self-produced feed reduced dependence on commercial feed by 20–30%, saving around IDR 1.5–2 million per cycle. Potential yields increased by 30–40%, while profits rose from IDR 3–4 million to IDR 5–6 million per cycle. These findings confirm that the program is effective and has the potential to deliver sustainable impacts on the welfare of the partner community.